From Durham to Brawner, A Futile Journey - Bernard L. Diamond (Washington University Law Quarterly, 1973)
I think it is fair to say that when Judge Bazelon revitalized the New Hampshire rule of 1869-1871 through Durham, he was hopeful of also revitalizing the cooperative, understanding, and progressive relationship between psychiatry and the law which those early New Hampshire decisions represented. Evidently Judge Bazelon was convinced that revision of the legal rules of insanity made in accord with the best available psychiatric advice and offering encouragement to the more progressive psychiatric promises of the time would result in real change, change of benefit both to the mentally ill offender and to the society victimized by his irrational behavior. The purpose of this Article is to discuss why such benefits have not materialized from Durham and why they should not be expected from Brawner or other recent modifications of the laws concerned with responsibility of mentally ill offenders.
Keywords: Brawner v. United States; 417 F.2d 969 (1972)